Development and validation of a UV/visible spectrophotometric method for simultaneous assay of paracetamol and ibuprofen - Mavanga Mabaya, Timothée; Mankulu Kakumba, Jocelyn; Mayangi Makola, Mannix; Mbenza Puati, Adelard; Mana Kialengila, Didi; Mavar Tayey Mbay, Jean; Mbinze Kindenge, Jérémie (Orapuh Journal, 2025)
Introduction The quality of medicines and healthcare products is a significant challenge these days, with counterfeiting accounting for at least 10% of all products in circulation worldwide, including in Africa. In the specific case of the Democratic Republic of Congo (DR Congo), which is the second-largest country on the continent and faces serious challenges in frontier control, the country has become a major hub for this scourge. Counterfeit medicines circulating within its territory account for over 20% of the pharmaceutical market. Purpose This research aimed to provide a simple, reliable, and economical method for quality control of drugs and healthcare products in the Congolese pharmaceutical market. This was achieved by developing and validating an ultraviolet-visible (UV-vis) spectrophotometric method for the simultaneous determination of paracetamol and ibuprofen in dosage forms. Methods From stock solutions, 0.65 ml of paracetamol and 0.8 ml of ibuprofen were transferred into volumetric flasks to prepare 10 ml of each solution. These solutions were separately scanned between 200-400 nm to observe the absorption maxima of each compound in UV-vis spectra against the blank (ethanol). Subsequently, individual solutions were prepared to obtain calibration and validation standards for the method validation, using the total error strategy and studying various validation criteria (specificity, precision, accuracy, linearity, robustness). After evaluating all the criteria, the developed and validated method was applied for the qualitative and quantitative analysis of dosage forms containing both paracetamol and ibuprofen. Results When solubilized in ethanol, paracetamol and ibuprofen exhibited absorption maxima at 249 nm and 219 nm, respectively. The method demonstrated strong correlation over the concentration ranges used (2.6–9.1 µg/ml for paracetamol and 3.2–9.6 µg/ml for ibuprofen). The correlation coefficients and regression lines determined at selected wavelengths were: y = 0.0924 x (R2 = 0.999) and y = 0.0228x (R2 = 0.9996) for paracetamol at 249 nm and 219 nm respectively, and y = 0.0429 x (R2 = 0.9993) for ibuprofen at 219 nm. The committed bias and the coefficient of variation in the precision study were within ±2% and less than 2%, respectively. Furthermore, the application of the method to dosage forms produced appropriate active ingredient rates, which ranged between 98% and 102%. Conclusion The developed method showed no interference between the active ingredients and the usual excipients used in tablet manufacturing. The recovery rates obtained in the selectivity and accuracy studies were consistently between 98% and 102%. Active ingredient contents determined by applying the method to pharmaceutical dosage forms ranged between 95% and 105%.